Complete chloroplast genome sequences of Mongolia medicine Artemisia frigida and phylogenetic relationships with other plants. - Yue Liu; Naxin Huo; Lingli Dong; Yi Wang; Shuixian Zhang; Hugh A Young; Xiaoxiao Feng; Yong Qiang Gu (PLoS ONE, 2013)
BACKGROUND: Artemisia frigida Willd. is an important Mongolian traditional medicinal plant with pharmacological functions of stanch and detumescence. However, there is little sequence and genomic information available for Artemisia frigida, which makes phylogenetic identification, evolutionary studies, and genetic improvement of its value very difficult. We report the complete chloroplast genome sequence of Artemisia frigida based on 454 pyrosequencing. METHODOLOGY/PRINCIPAL FINDINGS: The complete chloroplast genome of Artemisia frigida is 151,076 bp including a large single copy (LSC) region of 82,740 bp, a small single copy (SSC) region of 18,394 bp and a pair of inverted repeats (IRs) of 24,971 bp. The genome contains 114 unique genes and 18 duplicated genes. The chloroplast genome of Artemisia frigida contains a small 3.4 kb inversion within a large 23 kb inversion in the LSC region, a unique feature in Asteraceae. The gene order in the SSC region of Artemisia frigida is inverted compared with the other 6 Asteraceae species with the chloroplast genomes sequenced. This inversion is likely caused by an intramolecular recombination event only occurred in Artemisia frigida. The existence of rich SSR loci in the Artemisia frigida chloroplast genome provides a rare opportunity to study population genetics of this Mongolian medicinal plant. Phylogenetic analysis demonstrates a sister relationship between Artemisia frigida and four other species in Asteraceae, including Ageratina adenophora, Helianthus annuus, Guizotia abyssinica and Lactuca sativa, based on 61 protein-coding sequences. Furthermore, Artemisia frigida was placed in the tribe Anthemideae in the subfamily Asteroideae (Asteraceae) based on ndhF and trnL-F sequence comparisons. CONCLUSION: The chloroplast genome sequence of Artemisia frigida was assembled and analyzed in this study, representing the first plastid genome sequenced in the Anthemideae tribe. This complete chloroplast genome sequence will be useful for molecular ecology and molecular phylogeny studies within Artemisia species and also within the Asteraceae family.